Protection of Political Rights in Surabaya Regional Head Elections 2020 during the COVID 19 Pandemic - Iman Pasu Purba; Alifia Widianti; Irma Lianna (Musamus Law Review, 2021)
The state must be responsible for fulfilling the political rights of every citizen. Political rights are one of the human rights that cannot be reduced by the state. Even though Indonesia is currently experiencing the Covid 19 Pandemic, the Government decided to hold simultaneous local elections due to various considerations. As for some of these considerations is the need for legal certainty of the election of new public officials because the previous period is up, the Covid 19 pandemic is not known when it will end, the strategic policies of the government must still be taken and implemented, and the main thing is to fulfill the political rights of Indonesian citizens who are a democracy based on the law. Therefore, it is considered necessary to explore how the country fulfills the political rights of the citizens of Surabaya during the Pandemic at the Simultaneously Regional Head Elections 2020. This study is conducted with empirical normative where researchers will examine every rule relevant to this theme and empirically review the implementation of government rules and policies in the fulfillment of people's political rights at the 2020 Regional Elections and the obstacles faced in the fulfillment process.